Investigation of wettability measurements of protective gloves materials - Irzmańska, Emilia; Adamus-Włodarczyk, Agnieszka; Jastrzębska, Aleksandra; Litwicka, Natalia (Wydawnictwo Politechniki Łódzkiej, 2022)
Wettability measurements of the polymeric materials that are designed to be used for protective gloves are the key aspect in the evaluation of their potential safety of use. The gloves made of polymeric materials that will be resistant to chemical or biological contamination should exhibit low wettability and good adhesive properties to reduce the possibility of accumulation of hazardous substances on the surfaces of the gloves together with losing dexterity of hand movement during work. Currently, in laboratory practice, there is no method to investigate thoroughly the wetting properties of polymeric surfaces taking into consideration parameters like water permeability index, non-wettability index, and absorption index. The presented research concerns the novel way of measuring the wettability of polymeric protective gloves, and the validation of the proposed method. Based on the series of performed measurements, a thorough assessment of the uncertainty budgets for individual components of performed metrological analysis of obtained results was performed. Based on these findings, the measurement errors that could affect the reliability, repeatability, and quality of the performed investigation have been identified.
Keywords: wettability; protective gloves; validation; polymers; zwilżalność; rękawice ochronne; walidacja; polimery